Telemedicine-Enabled Bedside Monitoring System for Low-Birth-Weight Infants: Strengthening Primary Healthcare Resilience and Family-Centered Neonatal Care in Indonesia - Sari Luthfiyah; Bambang Guruh Irianto; Lusiana Lusiana; Abdul Kholiq; Syevana Dita Musvika; Much Faiz Nafi'u Pradana; Rifan Ramandani; Muhamad Muflih Ridwan (Frontiers in Community Service and Empowerment, 2026)
Low Birth Weight (LBW) remains a critical neonatal health problem due to its strong association with increased morbidity and mortality risks, requiring continuous and accurate physiological monitoring. This community service program aimed to implement a telemedicine-based bedside monitoring system at Gedangan Community Health Center, Sidoarjo Regency, to improve neonatal care services and strengthen health worker capacity in managing LBW infants. The intervention addressed key challenges, including limited access to real-time monitoring data, insufficient technological integration in primary care settings, and the need for improved technical competence among health workers. The method employed a structured community engagement approach consisting of counseling, training, demonstration, re-demonstration, and continuous mentoring. Thirty health workers, including nurses, midwives, and electromedical personnel, participated in the program conducted over two days. Evaluation was performed through direct oral questioning and structured practical observation during device operation and simulation activities. The results indicated a significant improvement in participants’ knowledge and skills, with an increase in understanding of neonatal monitoring concepts and telemedicine application. Participants demonstrated improved ability to operate the bedside monitor, interpret vital sign parameters, and apply standard operating procedures. However, post-implementation evaluation revealed partial non-compliance with SOPs in device operation, maintenance, and repair, highlighting the need for continuous training and supervision. The telemedicine system successfully enabled real-time transmission of neonatal physiological data, improving accessibility for both health workers and families. In conclusion, the implementation of a telemedicine-based bedside monitoring system effectively enhanced the capacity of primary healthcare services for LBW infants. Continuous mentoring, infrastructure support, and periodic training are essential to ensure sustainability and optimal utilization of the technology in neonatal care.